CONFIGURANDO OS CONTEXTOS DE OCORRÊNCIADOS PRETÉRITOS PERFEITO E MAIS-QUE-PERFEITO - Coan, Márluce (Organon, 2012)
This paper aims at dealing with anteriority to a past reference point,codified in Portuguese as “pretérito mais-que-perfeito composto” (pluperfect) or“pretérito perfeito” (simple past) verb forms, analysing data from “ProjetoVARSUL” (Variação Lingüística Urbana na Região Sul). The results havecharacterized the phenomenon as a complex functional domain, influenced bymotivations of a different nature: linguistic and social.